PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN MENYIMAK SISWA KELAS IV SDN 30 SINGKAWANG - Zubaidah; Eti Sunarsih; Emi Sulistri (STKIP Subang, 2026)
This research is motivated by the low listening skills of students and the lack of interest and focus of students in participating in learning Bahasa Indonesia. This study aims to find out the difference in students' listening skills before and after the implementation of the TGT (Team Games Tournament) type cooperative learning model assisted by audio visual media, find out the magnitude of the influence of the model, and describe the students' responses after participating in learning. This study uses a quantitative approach with a pre-experimental method and a one group pretest-posttest design. The population in this study is all grade IV students of SDN 30 Singkawang totaling 17 students, with sampling techniques using saturated sampling. The data collection technique uses a listening skills test and a student response questionnaire. Data analysis was carried out using the Shapiro-Wilk normality test, the paired sample t-test, the effect size test, and percentage analysis. The results showed that the average score of students' listening skills increased from 39.41 in the pretest to 77.64 in the posttest. The results of the paired sample t-test obtained a Sig. (2-tailed) value of 0.000 < 0.05, so that there was a significant difference between students' listening skills before and after the application of the learning model. The results of the effect size test obtained a score of 3.33 which is in the high category. Meanwhile, students' responses to the implementation of the TGT-type cooperative learning model assisted by audio visual media obtained an average percentage of 60.28% with a good category. Thus, the TGT type cooperative learning model assisted by audio-visual media has a high influence on improving the listening skills of fourth grade students of SDN 30 Singkawang.